Low-Temperature DC Carrier Transport in (Fe0.45Co0.45Zr0.10)x(Al2O3)1−x Nanocomposites Manufactured by Sputtering in Pure Ar Gas Atmosphere - Ivan A. Svito; Alexander K. Fedotov; Anis Saad; Momir Milosavljević; Julia A. Fedotova; Tomasz N. Kołtunowicz; Paweł Żukowski (Advances in Condensed Matter Physics)
This presented work investigates the structure and temperature relationship/dependence of the DC conductivity σ(T) in the (Fe0.45Co0.45Zr0.10)x(Al2O3)1−x nanocomposites deposited in Ar atmosphere with composition (30<x<100 at.%) and temperature (2<T<300 K). It is shown that VRH σ(T) displayed crossover from Mott-like to Shklovskii-Efros regimes which occurred at temperatures of 100–120 K. It is also noted that the observed shift of the percolation threshold to higher concentrations of metallic fraction can be attributed to the disordering of the metallic nanoparticles due to the incorporation of the residual oxygen in the vacuum chamber during the deposition procedure.